Effects of 1, 25-dihydroxyvitamin D3 on Inflammatory Responses of Stromal Vascular Cells and Adipocytes from Control and Obese Mice (FS12-04-19). (13th June 2019) - Park, Chan Yoon; Kim, Tae Yeon; Seo, Yeonkyung; Yoo, Ji Su; Pae, Munkyong; Han, Sung Nim
Abstract: Objectives: Several in vitro studies showed that 1, 25-dihydroxyvitamin D3 (1, 25(OH)2D3) treatment could inhibit chronic inflammation in mouse or human adipocytes; however there have been a few in vivo studies. We investigated whether vitamin D supplementation affects subpopulation of immune cells in adipose tissue and the effects of in vitro 1, 25(OH)2D3 treatment on pro-inflammatory cytokine secretion by stromal vascular cells (SVC) and adipocytes. Methods: Five-wk old C57BL/6 N mice were divided into 4 groups and fed diets differ in fat amount (10 or 45% kcal fat: CON or HFD) and vitamin D content (1000 or 10, 000 IU/kg of diet: DC, or DS) for 13 wks. Subpopulation of immune cells (macrophage, NK cell, CD 4 T cell, CD 8 T cell, B cell) from adipose tissue-derived SVC was determined by FACS analysis. Five-wk old C57BL/6 mice were fed control or HFD diets (10 or 60% kcal fat, CON or HFD) for 12 wks. Adipocytes and SVC, isolated from visceral adipose tissue, were cultured with or without 10 nM of 1, 25(OH)2D3 for 48 h and stimulated with LPS during the last 24 h. Pro-inflammatory cytokines produced by SVC and adipocytes were measured by ELISA. The mRNA levels of Tlr2, Tlr4, Dusp1, and Dusp10 were determined in SVC by real-time PCR. Results: The number of macrophages and NK cells within adipose tissue were higher in the HFD groups than CON groups. Dietary vitamin D did not alter the number of immune cells in adipose tissue. The production of IL-6 and MCP-1 from SVC and adipocytes were higher in the HFD groups compared with CON groups. In vitro 1, 25(OH)2D3 treatment decreased IL-6, MCP-1, IL-1β production by SVC from HFD group and decreased IL-6 production by SVC from CON group. SVC Tlr2 mRNA levels, which were higher in the HFD group, decreased significantly by in vitro 1, 25(OH)2D3 treatment. mRNA levels of Dusp1, which inhibits MAPK signaling, were increased by in vitro 1, 25(OH)2D3 treatment. However, pro-inflammatory cytokine secretion from adipocytes was not affected by in vitro 1, 25(OH)2D3 treatment. Conclusions: Although vitamin D supplementation did not reduce macrophage and NK cell numbers in adipose tissue, 1, 25(OH)2D3 seemed to decrease pro-inflammatory cytokine production from SVCs by regulating Tlr2 and Dusp1 . Funding Sources: Supported by the grant from the National Research Foundation (NRF) of Korea (NRF-2018R1D1A1B070491).